Factors influencing eruption time of first deciduous tooth. - Ghoncheh Vahdat; Mahdieh Zarabadipour; Farnoosh Fallahzadeh; Reza Khani (Universidad de Concepción., 2019)
Introduction: Deciduous teeth play an important role in proper growth. Tooth eruption is a complicated process in which different mechanisms are involved. Early or delayed tooth eruption depends on different factors, with the impact of some already established. There are apparent controversy regarding the effect of some factors on time of the first deciduous tooth eruption among the conducted studies. The current study aimed to evaluate factors affecting the time of the first deciduous tooth eruption. Materials and Methods: One hundred and sixty eligible infants referring to the healthcare centers of Tabriz, Iran, were randomly selected; the demographic data including weight and height at birth, head circumference, mother's age and level of education, birth rank in the family and type of feeding were recorded, in addition to the time of the first deciduous tooth eruption. Data were analyzed using SPSS version 21 by ANOVA and t test.Results: Out of 54.1% female and 45.9% male participating infants, 78.3% had normal weight at birth. Results showed a significant relationship between weight at birth and timing of the first deciduous tooth eruption, among the evaluated factors. Conclusions: Although no significant relationship was observed between gender, type of feeding, mother's level of education and birth rank in the family, and time of the first deciduous tooth eruption, there was a significant relationship between the weight at birth and the timing of the first deciduous tooth eruption. Infants with higher or lower abnormal weight at birth had delayed deciduous tooth eruption.